Primary hepatic leiomyosarcoma in a 5-month-old female infant. Issue 7 (18th November 2013) - Tsai, Pei-Shan; Yeh, Ting-Chi; Shih, Shin-Lin
Leiomyosarcoma is a malignant mesenchymal neoplasm deriving from the smooth muscle cells. Primary hepatic leiomyosarcoma is very rare. Its onset is always during middle and old age. Herein, we present a case of primary hepatic leiomyosarcoma in a 5-month-old girl who may be the youngest patient reported in the known published English literature.